Warren G. Magnuson and the shaping of twentieth-century America - Scates, Shelby (Emil and Kathleen Sick lecture-book series in western history and biography., 1997)
Warren G. Magnuson served as U.S. senator from the state of Washington for six terms. The sheer sweep of his accomplishments is astonishing: authoring the Civil Rights Act, protecting Puget Sound, saving Boeing for Seattle, championing consumer protection legislation, reorganizing the railroads, and godfathering the electrification of the Pacific Northwest by pressing for Columbia and Snake River dams. He pushed federal aid to education, while holding down Pentagon budgets, and established the National Institutes of Health (and kept research funds flowing liberally) while arguing throughout the McCarthy era against U.S. isolation from China. He did much more. But he was also a boon whiskey-and-poker companion to Presidents Roosevelt, Truman, Kennedy, and Johnson.